Draft genome sequence of Escherichia coli MTR_GS_S1457 strain isolated from a soil sample of a vegetable garden in Gazipur, Bangladesh - Islam, Md. Saiful; Pramanik, Pritom Kumar; Rana, Md. Liton; Ullah, Md. Ashek; Neloy, Fahim Haque; Ramasamy, Srinivasan; Schreinemachers, Pepijn; Oliva, Ricardo; Rahman, Md. Tanvir (American Society for Microbiology, 2024)
We announce the sequence of the Escherichia coli MTR_GS_S1457 strain isolated from a soil sample of a vegetable gardening system for the first time in Bangladesh. With a length of 4,918,647 bp, this strain contained one plasmid, two CRISPR arrays, 54 predicted antibiotic resistance genes, and 81 predicted virulence factor genes.